Business Events - Rob Davidson (New York Routledge, 2019)
The dynamic and fast-expanding business events sector plays a vital role in the professional lives of hundreds of millions of people worldwide by providing settings in which they can meet for the purposes of negotiation, deliberation, motivation, the dissemination of knowledge, and the celebration of their greatest career-related achievements. This book provides a sound practical and theoretical context for the study of this subject by covering, in depth, all categories of business-related events including corporate meetings, association conferences, political events, incentive travel, exhibitions, corporate hospitality, awards ceremonies and SMERF (social, military, educational, religious and fraternal) gatherings. This new edition has been extensively revised and updated to reflect recent developments in business events, including: Five new chapters on business events destination marketing, knowledge, sustainability, ethics and technology New 'It's my job' voice boxes offering practical insights from people employed in the business events industry A wide range of new case studies illustrating business events throughout the world, including emerging business events destinations such as Russia and the Middle East Written in an accessible yet analytical manner, Business Events is essential reading for all students of events, tourism and hospitality management.
Keywords: (ETB-2003) Conference and Events Management